2014
DOI: 10.4103/0972-6748.144955
|View full text |Cite
|
Sign up to set email alerts
|

Crosssectional study of quality of life after renal transplant in end stage renal disease

Abstract: Background:End stage renal disease (ERD) is a psychologically debilitating illness with considerable emotional morbidity. There is variation in quality of life and mental health status among recipients and donor at different stages of kidney transplantation.Materials and Methods:The study is an observational analytic study. Sample for the study comprised of forty (40) consecutive patients including 20 recipients and 20 donors of 20 kidney transplantations, male and female, and who themselves/whose relatives pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Within the first year after KT, studies using the SF-36 and the KDQOL reported consistently better post-transplant HRQOL in the physical HRQOL domain ‘general health’ (GH) and mental HRQOL domain ‘vitality’ (VT), as well as in the disease-specific HRQOL domain ‘effect of kidney disease’ (EKD) in both young [ 13 , 17 , 19–26 ] and elderly KTRs [ 28 ]. Two studies using the WHOQOL also showed improvement in physical HRQOL during the first year after KT [ 14 , 29 ]. In KTRs with a post-transplant time of 46 months, Shresth et al [ 16 ] found an increase in all mental, physical and disease-specific HRQOL domains compared with the preoperative HRQOL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the first year after KT, studies using the SF-36 and the KDQOL reported consistently better post-transplant HRQOL in the physical HRQOL domain ‘general health’ (GH) and mental HRQOL domain ‘vitality’ (VT), as well as in the disease-specific HRQOL domain ‘effect of kidney disease’ (EKD) in both young [ 13 , 17 , 19–26 ] and elderly KTRs [ 28 ]. Two studies using the WHOQOL also showed improvement in physical HRQOL during the first year after KT [ 14 , 29 ]. In KTRs with a post-transplant time of 46 months, Shresth et al [ 16 ] found an increase in all mental, physical and disease-specific HRQOL domains compared with the preoperative HRQOL.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this review suggest consistently better HRQOL in KTRs, including elderly KTRs, when compared with patients with ESKD [i.e. the same cohort pre-transplantation consisting of patients receiving dialysis or patients not receiving RRT with pre-emptive KT (PEKT) and patients receiving dialysis with or without being on the WL] [ 14–22 , 27 , 28 , 57 , 58 ]. Our findings are in line with the previous systematic review conducted by Liem et al [ 10 ] in 2007, showing higher HRQOL in physical (i.e.…”
Section: Discussionmentioning
confidence: 99%